As observed from the graph, the curve is a straight line from point (-2,-1) to (-5,2).
Consider that the equation of a straight line passing through two points is given by,
![y-y_1=(y_2-y_1)/(x_2-x_1)*(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/m7a3hf5yb78k7zc3hdk9nlctkaxukfi655.png)
So the equation of the line passing through (-2,-1) and (-5,2) is given by,
![\begin{gathered} y-(-1)=(2-(-1))/(-5-(-2))*(x-(-2)) \\ y+1=(3)/(-3)*(x+2) \\ y+1=-x-2 \\ y=-x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j3dgsj0kap27uynvjwhl5uhouhz9k016fc.png)
Note that this function is only for the interval [-2, -5].
Now, the value of 'y' corresponding to the input x=-4 is calculated as,
![\begin{gathered} y=-(-4)-3 \\ y=4-3 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/79d2d1es5fazksy7rp24yx8cvz0zvdxb4v.png)
Thus, the required output is y = 1 .